Taxation and Pricing of Petroleum Products in Developing Countries : A Framework for Analysis with Application to Nigeria - Hossain, Shahabuddin (IMF Working Papers; Working Paper ;, 2003)
Using the modern theory of public economics as the point of departure, this paper outlines a basic principle for setting taxes and/or prices of commodities based on two key criteria, efficiency and equity. The paper shows that for petroleum products, the basic principle needs modification in the presence of various externalities and market imperfections in a setting where the instruments to address the externalities and imperfections are limited. Drawing from theoretical and empirical literature, the paper provides an operational framework and then illustrates how, for a country like Nigeria, the relevant taxes/subsidies to correct the externalities and to address equity and revenue considerations can be measured with a view to setting prices of petroleum products. However, the paper refrains from making any specific suggestion for policy reform in Nigeria. The framework outlined in the paper can be applied to the analysis of petroleum product taxes and prices in other developing countries.